Anti‐incretin effect: The other face of Janus in human glucose homeostasis. (26th July 2019) - Karras, Spyridon N.; Koufakis, Theocharis; Mustafa, Omar G.; Kotsa, Kalliopi
Summary: The provocative idea that type 2 diabetes (T2D) may be a surgically treated disorder is based on accumulating evidence suggesting impressive remission rates of obesity and diabetes following bariatric surgery interventions. According to the "anti‐incretin" theory, ingestion of food in the gastrointestinal (GI) tract, apart from activating the well‐described incretin effect, also results in the parallel stimulation of a series of negative feedback mechanisms (anti‐incretin effect). The primary goal of these regulations is to counteract the effects of incretins and other postprandial glucose‐lowering adaptive mechanisms. Disruption of the equilibrium between incretins and anti‐incretins could be an additional pathway leading to the development of insulin resistance and hyperglycemia. This theory provides an alternative theoretical framework to explain the mechanisms behind the optimal effects of metabolic surgery on T2D and underlines the importance of the GI tract in the homeostatic regulation of energy balance in humans. The anti‐incretin concept is currently based on a limited amount of evidence and certainly requires further validation by additional studies. The aim of the present review is to discuss and critically evaluate recent evidence on the anti‐incretin theory, providing an insight into current state and future perspectives.